Membangun Generasi Qur'ani: Website Interaktif Belajar Agama Islam untuk Anak SD - Nugi Agasit; Alvito Apta Abimanyu; Rey Valentino (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This article describes the development process of the Islamic Learning Media website as an innovative online educational tool designed to support Islamic learning for elementary school students. The study employed a mixed-methods approach, combining qualitative methods to examine the website’s design components, information structure, navigation system, and platform interface with quantitative methods through the distribution of a questionnaire using Google Forms to 42 respondents to evaluate the website’s feasibility and usability. A key focus of this study is how contemporary visual design, attractive layouts, and distinctive typography can enhance the delivery of religious content in a more engaging, accessible, and user-friendly manner for young learners. The findings indicate that the integration of a child-friendly user interface design contributes positively to students’ learning experiences by improving readability, ease of navigation, and overall user satisfaction. The evaluation results showed an average score of 4.48 out of 5.00, with 95.24% of respondents rating the website as Good or Excellent. These findings suggest that the website functions as an informative, interactive, and effective learning medium that supports Islamic education while increasing students’ interest and engagement in digital learning environments.